Clinical and radiographic results of the use of a titanium wedge in pediatric patients undergoing calcaneal lengthening osteotomy for symptomatic flat foot - Di Grigoli, Cristina; Giarratana, Laura Serena; Croci, Gabriele; Monforte, Sergio; Canavese, Federico; Andreacchio, Antonio (Journal of pediatric orthopaedics. B, 2025)
Flatfoot is a common condition in children; surgical treatment should be reserved for severe and symptomatic cases. Calcaneal lengthening osteotomy (CLO) has been associated with good results; the original technique considers the use of allografts or autografts. This study aimed to evaluate advantages of a titanium trapezoidal wedge (TTW) in a pediatric population, compared with traditional grafts. At our knowledge, there are no studies in pediatric patients. This is a retrospective study of 11 patients (14 feet) with severe flatfoot treated with CLO and TTW and a control group of nine patients (13 feet) treated with CLO and traditional grafts. The mean age of TTW group was 13.4 years, and the mean follow-up was 15 months. The mean age in the control group was 13.7 years, and the mean follow-up was 36 months. Pre- and postoperative clinical and radiographic measures were evaluated, as well as operative time and radiation exposure. At follow-up, feet treated with TTW showed an improvement in all radiographic parameters measured on weight-bearing radiographs and also an improvement in the American Orthopedic Foot and Ankle Society Score, comparable to the control group. The use of TTW significantly reduced radiation exposure and operating time. No cases of graft fracture or migration were observed. All TTW appeared osteointegrated at the last follow-up. CLO using TTW is an effective procedure, allows correction to be maintained over time and reduces operative time and radiation exposure. Despite the promising results, our findings should be considered as a preliminary report; more data are needed to confirm our results.